PENINGKATAN MUTU PENDIDIKAN MELALUI SINERGI KEBIJAKAN ANTARA PEMERINTAH PROVINSI, KABUPATEN, DAN KOTA - Ridwan Saifuddin (Inovasi Pembangunan : Jurnal Kelitbangan, 2019)
Abstract: This study aims to identify forms of synergy between provincial, districts, and city governments in the management of primary and secondary education by involving cross-stakeholders. This study uses a qualitative method. The conclusion of this research is the development of the education sector cannot be done partially. Institutions are needed for coordination, integration, and acceleration of the increase and even distribution of quality of education in Lampung Province, which represents provincial, districts, and city level policy makers. Increasing teacher competency needs to be a priority of the provincial, districts, and city governments in efforts to improve and evenly distribute the quality of primary and secondary education, including the ability and mastery of soft skills. Supporting infrastructure also determines the success of the development of the education sector. Provincial, districts, and city governments also need to develop special learning models, aimed at students with special intelligence and talent potential. Keywords: synergy, development, competence, education, infrastructure.